Risk and residency influences on public support for florida panther recovery - Cynthia Langin; Susan K. Jacobson (Wildlife Society Bulletin)
Abstract Human expansion into core habitat of the Florida panther (Puma concolor coryi) increasingly threatens this endangered carnivore. To understand the social dimensions of the influence of humans' proximity to risk from panthers on public support for panther recovery, a telephone survey was conducted in March 2007 on a random sample of 802 Florida, USA, residents stratified by 1) location in core Florida panther habitat in Southwest Florida or noncore potential translocation sites in South Central Florida, and 2) rural or urban residence. Respondents reported a moderate intention to support panther recovery. Few attitudinal differences were found between urban versus rural and core versus noncore residents. However, core urban residents scored higher on a knowledge index than did rural residents. Regression analysis of behavioral intentions to support panther recovery identified management preferences, perceptions, subjective norm, knowledge, duration of Florida residence, and level of interest in wildlife as predictors. The resulting model (R2 = 0.42) is effective for predicting support and providing insight into the characteristics associated with willingness to support panther recovery. © 2012 The Wildlife Society.